PERANAN SULTAN MAHMUD BADARUDDIN II DALAM PERANG PALEMBANG 1819-1821 - Ariyanto, Rizky (KARMAWIBANGGA Historical Studies Journal, 2020)
This study aims to: (1) describe and analyze the background and life history of Sultan Mahmud Badaruddin II; (2) describe and analyze the Palembang War 1819-1821; (3) describe and analyze the role of Sultan Mahmud Badaruddin II in the Palembang War 1819-1821; (4) describe and analyze the impact of the Palembang War 1819-1821. This research uses literature method. Data collection is done by collecting written data sources through literature studies in books, journals, theses and the internet. The steps in the research are as follows; heuristics, source criticism and interpretation and historiography.  The results of this study indicate that: (1) Sultan Mahmud Badaruddin II is the Sultanate of the Palembang Darussalam Sultanate who is wise in carrying out his leadership; (2) The Palembang War 1819-1821 was divided into three periods, two periods in 1819 and one period in 1821; (3) the Sultan Mahmud Badaruddin II resisted the Dutch, who were far superior in weaponry and were able to win the Palembang War in 1819 twice; (4) the impact of this war, namely blocking the Sunsang estuary, abolishing the sultanate and replacing it with residency.